2013
DOI: 10.1073/pnas.1200338110
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of aldoxime dehydratase and its catalytic mechanism involved in carbon-nitrogen triple-bond synthesis

Abstract: Aldoxime dehydratase (OxdA), which is a unique heme protein, catalyzes the dehydration of an aldoxime to a nitrile even in the presence of water in the reaction mixture. Unlike the utilization of H 2 O 2 or O 2 as a mediator of catalysis by other heme-containing enzymes (e.g., P450), OxdA is notable for the direct binding of a substrate to the heme iron. Here, we determined the crystal structure of OxdA. We then constructed OxdA mutants in which each of the polar amino acids lying within ∼6 Å of the iron atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 47 publications
3
54
0
Order By: Relevance
“…27,28 Like Clds and DyPs, they have a proximally histidine-ligated heme and a mostly-hydrophobic distal pocket. However, unlike Clds or DyPs, OxdAs are catalytically active in the ferrous form, and the substrate-bound ferric form of the protein is catalytically dead.…”
Section: Understanding Function: Heme As a Cofactormentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Like Clds and DyPs, they have a proximally histidine-ligated heme and a mostly-hydrophobic distal pocket. However, unlike Clds or DyPs, OxdAs are catalytically active in the ferrous form, and the substrate-bound ferric form of the protein is catalytically dead.…”
Section: Understanding Function: Heme As a Cofactormentioning
confidence: 99%
“…28 The aldoxime (R-CH=NOH) substrate directly binds the heme iron through its nitrogen atom, 27 where it forms hydrogen bonds to conserved serine and histidine residues through its –OH group. The histidine is adjacent to a conserved arginine which, like in the canonical peroxidases, is an arrangement that is proposed to stabilize the distal histidine in its neutral/deprotonated form.…”
Section: Understanding Function: Heme As a Cofactormentioning
confidence: 99%
“…The active site of N-substituted formamide deformylase has never been identified experimentally. Further studies on N-substituted formamide deformylase from the standpoint of its three-dimensional structure could provide information about the evolutionary relationship of this enzyme and other enzymes involved in the cleavage and synthesis of a C-N bond, such as nitrilase (56,57), nitrile hydratase (58), amidase (49,50), and aldoxime dehydratase (59).…”
Section: Discussionmentioning
confidence: 99%
“…(Konishi et al, 2006;Nomura et al, 2013) of nitriles not only from a basic standpoint but also from an applied point of view (Herai et al, 2004;Kobayashi and Shimizu, 1998;Komeda et al, 1996b).It has been reported that microorganisms and plants can degrade cyanides to less toxic compounds through biochemical reactions. Some of these are degradative pathways involving cyanide hydratase, nitrile hydratase, cyanidase, nitrilase, thiocyanate hydrolase, cyanide dioxygenase and cyanase.…”
mentioning
confidence: 99%
“…(Konishi et al, 2006;Nomura et al, 2013) of nitriles not only from a basic standpoint but also from an applied point of view (Herai et al, 2004;Kobayashi and Shimizu, 1998;Komeda et al, 1996b).…”
mentioning
confidence: 99%